2007
DOI: 10.1177/0021943607306138
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceptions of Journal Quality on Business and Management Communication Academics

Abstract: This commentary describes and critiques criteria that, according to results from an Association for Business Communication (ABC) member survey, are having an impact on quality judgments about our journals. ABC members rank the Journal of Business Communication and Business Communication Quarterly as top research and pedagogical journals in business/management communication, a finding corroborated by a larger study of academics in business and technical communication. However, the growing importance of citation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 26 publications
2
21
1
Order By: Relevance
“…Findings reveal reviewers' diverse perceptions of the norms of academic writing and of their positioning in relation to authors which broadly mirror the findings of Rentz (2005) and Rogers, Campbell, Louhiala-Salminen, Rentz, and Suchan (2007) in internal studies into editorial board members at the Journal of Business Communication (Sage Publications). As a response to the findings from research particularly into the Asian EFL Journal, alternative review criteria and a looser review procedure to the ones existing for research paper submissions was devised for papers which fell outside the standard form of academic writing and structure, termed as 'Alternative Voice' (Nunn & Adamson, 2009).…”
Section: Literature Reviewsupporting
confidence: 68%
“…Findings reveal reviewers' diverse perceptions of the norms of academic writing and of their positioning in relation to authors which broadly mirror the findings of Rentz (2005) and Rogers, Campbell, Louhiala-Salminen, Rentz, and Suchan (2007) in internal studies into editorial board members at the Journal of Business Communication (Sage Publications). As a response to the findings from research particularly into the Asian EFL Journal, alternative review criteria and a looser review procedure to the ones existing for research paper submissions was devised for papers which fell outside the standard form of academic writing and structure, termed as 'Alternative Voice' (Nunn & Adamson, 2009).…”
Section: Literature Reviewsupporting
confidence: 68%
“…And when institutions heard they were to be rewarded for their research active staff in the 2001 RAE, co‐authorship proliferated (Moed, ; see also Bence and Oppenheim, ). AIM senior fellows themselves reported that the scholarship demanded for the 2008 RAE had induced a third of academics to shift their publication from practitioner journals (Salter et al ., , p. 29; see also Rogers et al ., ). They also deserted other forms of output: while only 69% of RAE submissions in 1996 were journal papers, the 2008 figure was 92% (Mingers, Watson and Scaparra, ).…”
Section: The Publishing Elitementioning
confidence: 97%
“…One measure of the quality of scholarly journals is the acceptance rate of that journal (Barrows 2011;Suchan 2008). The logic is that a high quality journal will have a low acceptance rate; with the rationale that these are the journals with the most submissions and therefore can be the most selective of the best quality options-the lower the acceptance rate, the more discriminating the journal (Rogers et al 2007). …”
Section: Measuring Journal Quality Through Acceptance Rate Datamentioning
confidence: 99%
“…But when the product is scholarship (a product that exists through words and images in the mind), how can the illusive and inherently subjective goal of quality be measured consistently and fairly? The academic community attempts to do so, with measurements of citation impact factors, inclusion in major indexes, perception of senior researchers, endorsements by professional organizations, editor's reputation, review board affiliations or with the measurement of acceptance rates (Rogers et al 2007), a measure that is "becoming a more important metric" in promotion and tenure cases (Barrows 2011, p. 6).…”
mentioning
confidence: 99%